1990
DOI: 10.1016/s0022-5347(17)39923-8
|View full text |Cite
|
Sign up to set email alerts
|

Laxative Abuse as a Cause for Ammonium Urate Renal Calculi

Abstract: Nine women with laxative abuse and predominantly ammonium urate renal calculi underwent metabolic studies to identify common chemical abnormalities and determine pathophysiology. The 24-hour urine studies demonstrated marked decreases in volume (902 cm.3), sodium (28 mEq.), citrate (116 mg.) and potassium (21 mEq.). A significant elevation in ammonium urate supersaturation was found compared to control subjects when studied by the computer model EQUIL 2. Of the patients 7 had 1 or more urine specimens positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 14 publications
2
32
1
Order By: Relevance
“…For comparison, SI NH 4 U in one study of non-stone forming humans fed a standard metabolic diet was 1.5±0.9 (unpublished data). The preponderance of urinary ammonium over other urinary cations in the study dolphins is analogous to conditions reported in humans with NH 4 U stones 4-6, 24 .…”
Section: Discussionsupporting
confidence: 80%
“…For comparison, SI NH 4 U in one study of non-stone forming humans fed a standard metabolic diet was 1.5±0.9 (unpublished data). The preponderance of urinary ammonium over other urinary cations in the study dolphins is analogous to conditions reported in humans with NH 4 U stones 4-6, 24 .…”
Section: Discussionsupporting
confidence: 80%
“…Urinary ammonium and urate concentration should be high in order for AAU stones to develop. In addition, urine pH should be between 6.0 and 6.3 10 . Ammonia is produced in the proximal tubular cells in kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The low urinary sodium owing to severe diarrhea allows for the coupling of urate with the abundant ammonium ion. This coupling, combined with at least a transient state of ammonium urate supersaturation, promotes the formation of AAU stones [9]. This mechanism is similar to that for the formation of stones induced by rotavirus in infants.…”
Section: Discussionmentioning
confidence: 99%